An Investigation of ICT Usage in English Second Language Teaching and Learning in Zimbabwean Rural Secondary Schools - Mukomana, Saziso (University of the Witwatersrand, Johannesburg, 2025)
The advancement of a nation and the social development of its citizens depend heavily on the utilisation of technology in education. This study set out to investigate how ICTs are utilised in Zimbabwe’s rural secondary schools to teach and learn ESL. The theoretical framework that combined constructivism, behaviourism, and connectivism to research how ICTs are used in classroom instruction contexts served as the foundation for this study. Utilising a research approach of mixed methods, the study gathered information using both quantitative and qualitative methodologies. A research design that was sequential and explanatory was used. The quantitative phase used questionnaires to collect data from 120 learners and 3 ESL teachers. The qualitative phase gathered data through three groups of learners’ focus group discussions, three teacher individual semi-structured interviews, and four lesson observations. The results showed that teachers and learners recognised the advantages of ICTs in facilitating better methodological strategies. The findings also showed ICTs as increasing collaboration between teachers and learners while creating better access to necessary information, and promoting ESL classes with the capacity to accommodate learners with varying potential and learning preferences. The findings from the research showed that a variety of challenges, which include lack of ICT skills among instructors, inadequate training, and low teacher confidence, made it difficult for rural secondary schools to effectively employ ICTs to teach ESL. The study recommended that for facilitators and learners to utilise ICTs successfully, more frequent workshops that concentrate on developing ICT skills in line with competency levels are necessary. The study also suggested that teachers should allow themselves to pick up certain technology-related abilities, even from some of their ICT literate learners. This will assist teachers in becoming more adept and self-assured ICT users.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy Division of Languages, Literacies and Literatures (School of Education), to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2025
Keywords: Information and Communication Technology; Teaching and Learning; Secondary schools in rural areas; ESL; Learning theories; Mixed Methods Research (MMR); UCTD; SDG-4: Quality education; SDG-9: Industry, innovation and infrastructure